PENGARUH PENETAPAN HARGA JUAL TERHADAP PENJUALAN PADA PT. XYZ GARMENT INDUSTRY - Yulifati Laoli; Mardelia Desfrida, Ratna, Tosanov T.P. Napitupulu, Raina Rosanti (Jurnal Ekonomi dan Bisnis, 2024)
The Influence of Selling Price Pricing On Sales At PT. XYZ Garment Industry. This study aims to determine: (1) the influence of selling price determination on sales at PT. XYZ Garment Industry. Variables used in this study are selling price (X) and sales (Y). Sample used in this research is report of production cost from year 2012-2022 counted 36 sample. The analysis used is Multiple Linear Regression Analysis. The analysis used to see the extent to which the data influence partially or simultaneously, the test results partially states that thitung> ttable (68.860> 2.034), means H0 rejected Ha accepted. While the test results simultaneously state that Fcount> Ftable (2320,740> 3,28), means Ha accepted H0 rejected, which means simultaneously Cost of Production and Sales Price significantly influence Sales at PT. XYZ Garment Industry. Based on the results of the analysis shows that the variable cost of production and selling prices have an influence on sales of 99.2%, and the rest of 0.8% influenced from factors not examined in this study by the author.